Electrothermally tunable morphological and redox design of heterogeneous Pd/PdxOy/carbon for humidity-hydron-driven energy harvesters. (May 2022) - Seo, Byungseok; Kim, Woosung; Park, Seonghyun; Song, Chanho; Kim, Sungsoo; Choi, Wonjoon
Abstract: Rational design of morphological and redox properties is essential for metal/metal oxides/carbon-based electrochemical electrodes. However, their conventional fabrication and screening entail time-consuming and complex processes involving phase and interface segregation, making it difficult to fully integrate the advantages of individual constituents. Here, we report an electrothermally tunable morphological and redox design of heterogeneous Pd/Pdx Oy /carbon for humidity-hydron-driven energy harvester (H-dEHs). Electrothermal waves (ETWs) triggered by Joule heating induce thermochemical reactions ( 2000 °C) passing through precursors of Pd nitrates and carbon within seconds. The programmable power and duration of single and multiple ETW pulses facilitate morphological and compositional traps capturing metastable phases of thermodynamically dispersed Pd species anchored on carbon fibers. The phase maps considering the threshold of structural and chemical transition offer fast screening of optimal Pd/Pdx Oy /carbon electrodes for H-dEHs fabricated by combining the active materials with poly(4-styrenesulfonic acid), thereby generating sustainable potential up to 3.9 V for 350 h, using ambient humidity as the stimulus. The ETW-based design strategy will inspire extremely rapid, yet precisely controlled fabrication routes to sorting and optimizing complex properties of heterogeneous materials, potentially useful for diverse applications, such as energy harvesting devices, electrochemical cells, catalysts, electromagnetic shielding, and sensors. Graphical Abstract: ga1 Highlights: Electrothermal waves (ETW) offer adjustable temperature ranges and heating–cooling rates for complex material synthesis. It enables the selective morphological and redox design of heterogeneous Pd/Pdx Oy @C electrodes. A phase map considering the threshold of structural and chemical transition induced by ETWs processing is established. It offers a fast screening of optimal Pd/Pdx Oy @C electrodes for humidity-hydron-driven energy harvesters (H-dEHs). They exhibit the outstanding potential and energy harvesting stability up to 3.9 V for 350 h under ambient humidity.